Arsenic pollution of agricultural soils by concentrated animal feeding operations (CAFOs). (January 2015) - Liu, Xueping; Zhang, Wenfeng; Hu, Yuanan; Hu, Erdan; Xie, Xiande; Wang, Lingling; Cheng, Hefa
Highlights: Animal wastes bearing organoarsenic feed additives can cause soil As pollution. Soil As levels were elevated in the CAFO zone compared to other agricultural lands. p -Arsanilic acid was widely detected in the environmental matrices of the CAFO zone. ASA was a significant source of As in the surface soils of the CAFO zone. Release of As from swine farms is an environmental problem worthy of attention. Abstract: Animal wastes from concentrated animal feeding operations (CAFOs) can cause soil arsenic pollution due to the widespread use of organoarsenic feed additives. This study investigated the arsenic pollution of surface soils in a typical CAFO zone, in comparison with that of agricultural soils in the Pearl River Delta, China. The mean soil arsenic contents in the CAFO zone were elevated compared to those in the local background and agricultural soils of the Pearl River Delta region. Chemical speciation analysis showed that the soils in the CAFO zone were clearly contaminated by the organoarsenic feed additive, p -arsanilic acid (ASA). Transformation of ASA to inorganic arsenic (arsenite and arsenate) in the surface soils was also observed. Although the potential ecological risk posed by the arsenic in the surface soils was relatively low in the CAFO zone, continuous discharge of organoarsenic feed additives could cause accumulation of arsenic and thus deserves significant attention.